Marketing Communication Strategy of "Persebaya Fourth Jersey 2024" Through Instagram @persebayastore - Ahmad Khoirul Hakim; Arfiyansyah; Salahudin Al Afgan; Yuga Adi Kusuma (DIGICOM : Jurnal Komunikasi dan Media, 2025)
This study aims to analyze the marketing communication strategy implemented by Persebaya Store in promoting the "Fourth Jersey 2024" through the Instagram account @persebayastore. The research employs a descriptive qualitative method, with data collected through interviews and observations. The findings reveal that the marketing strategy includes optimizing Instagram features such as Stories, Reels, Carousel, and collaborations with influencers. This strategy successfully achieves three stages of consumer transformation: changes in knowledge, attitude, and behavior. The study contributes to the understanding of social media integration in marketing communication, particularly in the sports merchandise industry.